Universality of the Enzyme Molecule - Shonukan, Olusola Olusoji (Obafemi Awolowo University Press, 2013)
Enzymes are complex proteins that cause a specific chemical change in other substances without being changed themselves. An enzyme is also a protein that is synthesized in a living cell and catalyzes or speeds up a thermodynamically possible reaction so that the rate of the reaction is compatible with the biochemical process essential for the maintenance of a cell. The enzyme in no way modifies the equilibrium constant or the AG of a reaction. As the title of the lecture states, enzymes are found in all living things and perform specific functions in them and they are applied in many disciplines including Medicine, Biochemistry, and Microbiology and in Industrial processes.